2022
DOI: 10.3390/jcm11206079
|View full text |Cite
|
Sign up to set email alerts
|

A Split Face Comparative Study to Evaluate the Efficacy of 40% Pyruvic Acid vs. Microdermabrasion with 40% Pyruvic Acid on Biomechanical Skin Parameters in the Treatment of Acne Vulgaris

Abstract: The synergy of cosmetic acids, with their keratolytic and antibacterial properties, with the mechanical exfoliation of the epidermis brings faster and better treatment results. The aim of the study was to compare the effects of using only pyruvic acid and the synergy of microdermabrasion and chemical exfoliation. In total, 14 women diagnosed with acne took part in the study. Two areas were marked on the participants’ faces: the right side (microdermabrasion treatment and a preparation containing pyruvic acid 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…After the entire treatment series, it was observed that microdermabrasion combined with pyruvic acid led to better results with increased hydration and reduced sebum secretion than using only the pyruvic acid treatment. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the entire treatment series, it was observed that microdermabrasion combined with pyruvic acid led to better results with increased hydration and reduced sebum secretion than using only the pyruvic acid treatment. 15 …”
Section: Discussionmentioning
confidence: 99%
“…After the entire treatment series, it was observed that microdermabrasion combined with pyruvic acid led to better results with increased hydration and reduced sebum secretion than using only the pyruvic acid treatment. 15 Chilicka et al 16 in a study using equipment for hydrogen purification and the mixture of cosmetic acids showed that hydrogen purification alone and combining this treatment with acids improved the patients' skin condition. However, the combined treatments showed better results in reducing skin eruptions and improving hydration or reducing sebum from the epidermal surface.…”
Section: Discussionmentioning
confidence: 99%
“…Given the virtually ubiquitous nature of acne in teenagers, there remains an appreciable need for novel therapies. Some new approaches include oxybrasion, 3 microdermabrasion with Pyruvic acid, 4 and cosmetic acids 5 …”
Section: Introductionmentioning
confidence: 99%
“…The best results are achieved when treatments are performed every 3-4 weeks. The number of treatments in a series depends on the treatment indications and the condition of the client's skin [27][28][29][30].…”
mentioning
confidence: 99%